Efektivitas Metode McKenzie dalam Mengurangi Intensitas Nyeri terhadap Low Back Pain: Literature Review - Ghistavera Izvantia; Ahmad Fauzi; Nisa Karima; Dyah Wulan Sumekar Rengganis Wardani (Pusat Riset dan Inovasi Nasional, 2025)
Low Back Pain is a degenerative disease that causes pain or discomfort in the 5th lumbar vertebra to the 1st sarcosacral vertebra. Low Back Pain itself is still one of the top five conditions that cause state losses in the world because it causes disability in sufferers. Non-pharmacological therapy for low back pain is McKenzie therapy. This study aims to see the effectiveness of McKenzie therapy in low back pain sufferers by searching the literature through the PubMed website, Google Scholar, Cochrane, and other scientific journal websites with the keyword